DASHBOARD PENJUALAN DAN PEMBELIAN PT PETRA SEJAHTERA ABADI - Utari Apriani; Dedi Trisnawarman; Zyad Rusdi (Fakultas Teknologi Informasi Universitas Tarumanagara, 2019)
Data warehouse is part of BI that can facilitate managers in analyzing data. From these data can be made as an input design dashboard. The purpose of this thesis is to design a data warehouse and dashboard design. The process used for the data warehouse is data mart, OLAP, OLTP, dimension table and fact table. The method used in making the dashboard is Requirements Prototype which has 7 stages consisting of needs analysis, making prototypes, adjusting prototypes with user desires, creating new systems, testing systems, adjusting user desires and using the system. The results of this system are expected to be visually clearly visible to the management of PT Petra Sejahtera Abadi and facilitate the analysis of sales and purchase developments and support company management in making decisions.